2020
DOI: 10.1002/cc.20390
|View full text |Cite
|
Sign up to set email alerts
|

Challenging Deficit Views of Latinx Students: A Strength‐based Perspective

Abstract: This chapter describes various strength‐based theoretical perspectives useful in understanding the experiences of Latinx community college students. We highlight key findings from studies that utilized these perspectives and conclude with recommendations for practitioners and leaders to consider as they support Latinx students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…There are various examples in the literature on validating curricula and pedagogies that were conducted in community college settings. First, Carales and López (2020) advocated for Ethnic Studies programs in community colleges to provide curricular experiences to Latina/o/x students that reflect their identities. Doran’s (2022) analysis of Chicana/o/x Studies programs in community colleges showed that many HSCCs, particularly in the Southwest, already offer these classes but that their presence and campus impact has been understudied.…”
Section: Applying the Servingness Framework To The Literature On Hsccsmentioning
confidence: 99%
“…There are various examples in the literature on validating curricula and pedagogies that were conducted in community college settings. First, Carales and López (2020) advocated for Ethnic Studies programs in community colleges to provide curricular experiences to Latina/o/x students that reflect their identities. Doran’s (2022) analysis of Chicana/o/x Studies programs in community colleges showed that many HSCCs, particularly in the Southwest, already offer these classes but that their presence and campus impact has been understudied.…”
Section: Applying the Servingness Framework To The Literature On Hsccsmentioning
confidence: 99%
“…The reach of Yosso’s framework is evidenced by a simple Google Scholar search, which yields over two million results and over 6,000 direct citations. Scholars applying Yosso’s frame expressly advance “asset-based” approaches to the study of Students of Color (e.g., Carales & López, 2020; Del Real Viramontes, 2020; Sáenz et al, 2017).…”
Section: Misinterpretations Of Bourdieu’s Work In Educational Researchmentioning
confidence: 99%
“…HSI Latinx students are likely to recommend these institutions to peers in their community (Núñez et al, 2011). Proximity to home and family is another reason that many Latinx students enroll in local community colleges or public universities (Carales & López, 2020; Contreras & Contreras, 2015); students who place a high value on staying close to home are more likely to attend an HSI or emerging HSI (Cuellar, 2012), which tends to be located where large numbers of Latinx live (Dayton et al, 2004). Latinas may experience pressure from family to stay close to home to fulfill familial roles, such as caring for younger siblings or helping with other household responsibilities (Gloria & Castellanos, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, it is also important to consider the agency that Latinas hold by enrolling in HSIs close to home. Carales and López (2020) argue that staying close to home for college should not be viewed from a deficit perspective as it is sometimes; instead, attention should be paid to the supportive role that family and community play for many Latinx college students (Kiyama & Rios-Aguilar, 2017; Matos, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%